A Bright Idea for Measuring Economic Growth - Henderson, Vernon; Storeygard, Adam; Weil, David N (American Economic Review, 2011)
The quantity of human-generated light visible from outer space reflects variation in both population density and income per capita. In this paper we explore the usefulness of the change in visible light as a measure of GDP growth. We discuss the data, and then present a statistical framework that uses lights growth to augment existing income growth measures, assuming that measurement errors in the two series are uncorrelated. For some countries with very poor income measurement, we significantly revise estimates of growth. Our technique also produces growth estimates for cities or regions where no other data are available.